Bone marrow findings in metastatic melanoma, including role of BRAF immunohistochemistry. (21st May 2019) - Corean, Jessica L. E.; George, Tracy I.; Patel, Jay L.; Li, K. David
Abstract: Introduction: We describe peripheral blood smear, bone marrow morphology, histopathology, immunohistochemistry, including BRAF V600E, and molecular testing results of patients with metastatic melanoma to the bone marrow. Methods: We performed a retrospective review for patients with metastatic melanoma to the bone marrow at our institution. Bone marrow morphology, histology, immunophenotyping, and cytogenetic/molecular genetic testing were reviewed, and BRAF V600E immunohistochemistry was performed. Results were compared to the literature. Results: We identified four patients with metastatic melanoma to the bone marrow presenting with at least one cytopenia. Two of the four patients had leukoerythroblastosis, with three patients having atypical cells on bone marrow aspirate/touch preparation, and all patients had aggregates of atypical cells on biopsy. Immunohistochemistry for S100, Melan A, and HMB45 confirmed the diagnosis in all patients, and BRAF V600E immunohistochemistry was detected in two of four patients, which correlated with molecular testing findings. Review of the literature found 27 total patients, with normocytic anemia and leukoerythroblastosis as common peripheral blood smear findings. Conclusions: Features including cytopenias (typically anemia), leukoerythroblastosis, and morphology of cohesive, large atypical cells in aspirate and biopsy, and immunohistochemical expression for S100, Melan A, and HMB45 were present in patients with metastatic melanoma. BRAF V600E immunohistochemistry is useful as a surrogate marker of molecular results. Regardless of clinical history, at the time of the bone marrow biopsies, hematologic malignancies are in the main differential diagnosis and very rarely included metastatic melanoma, likely due to the under‐recognized metastatic potential of melanoma to the bone marrow.